(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Displaced fractures of mid third clavicle are common in young athletic population and choice of management is still controversial. Recent studies have shown that these fractures do not have favourable outcomes with non-operative management and nonunion rates could be as high as 20%, in addition, there is symptomatic malunion with shortening. Objective: To compare the results of the operative versus that of conservative treatment for the management of displaced midshaft clavicular fractures. Materials and Methods: This prospective cross-sectional study was carried out in Orthopaedic and Trauma center, CMH, Dhaka, from the period of January 2014 to December 2016 to compare results of open reduction and internal fixation by plating with that of conservative management. Total 60 patients (30 in each group) were analyzed in terms of fracture union and functional outcome. Patients in the non-operative group were managed by triangular sling with or without strapping whereas in the operative group fractures were reduced and fixed with a contoured reconstruction plate. Patients were actively followed up for 12 months and functional outcome was measured by Rowe and Oxford shoulder scoring system. Complications were monitored clinically and radiologically. Results: All fractures in the operated group united compared with thirteen cases of symptomatic malunion (43.33%) in the non-operated group which is statistically significant. Rowe and Oxford scores was significantly higher in the operated group than the non-operated group in every occasion of follow-up. There was no major complication of surgery. In one patient (3.33%) plate had to be removed for hardware irritation and prominence. Conclusion: Open reduction and internal plate fixation in acute displaced midshaft clavicular fractures resulted in improved outcome decreased rate of non-union and symptomatic mal-union compared with non-operative treatment Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 81-85